Knowledge and attitude of private oral health-care practitioners about antimicrobial drugs prescription in the management of periodontal diseases: A cross-sectional observational survey - Ashish Bali; Amarpreet Singh; Prashant Pathania; Pankaj Chauhan; Shubh Karmanjit Singh Bawa (Wolters Kluwer Medknow Publications, 2020)
Background and Aim: The present study aimed to evaluate the knowledge and attitude of antimicrobial drugs prescribing by oral private health-care practitioners in the management of periodontal diseases across Mandi, Himachal Pradesh, India. Design: This was a descriptive cross-sectional percentage-based survey. Materials and Methods: A descriptive observational cross-sectional Study was conducted with the pretested and structured questionnaires which were sent physically to private oral health-care practitioners of Mandi district of Himachal Pradesh, India. The study was carried out for 2 months. A self-orchestrated questionnaire comprising 10 questions was sent by dental students to private practitioners of Mandi to assess their awareness along with a point of view concerning antimicrobial drugs prescribing for periodontal diseases. Facts entered in an Excel file were examined using SPSS version 22. Illustrative stats were carried out. Results: The survey was responded by 100 private practitioners providing oral health care who accomplish the questionnaire. Most of the private practitioners were in the age group of 20 and 60 years, and 63% were male and 37% were female. There was a statistically significant difference between knowledge on prescribing antimicrobial drugs by private oral health-care providers in Mandi, Himachal Pradesh, India. Amoxicillin Alone, amoxicillin with clavulanic acid and metronidazole was the most prescribing drug followed by clindamycin by private oral healthcare Practitioners in the management of periodontal diseases. Conclusion: Most of the private oral health-care providers practicing in Mandi, Himachal Pradesh, routinely prescribed prophylactic antimicrobial drugs, and the observational survey outcome shows that although the private practitioners do know about the antimicrobial drugs, they should be very careful while prescribing antimicrobial drugs in the management of periodontal diseases. Because of increasing microbial resistance, an immediate remedy is the need of the hour to tackle the devastating consequences of antimicrobial drugs resistance.